Spotlight on very-low-density lipoprotein as a driver of cardiometabolic disorders: Implications for disease progression and mechanistic insights - Lee, Hsiang-Chun; Akhmedov, Alexander; Chen, Chu-Huang (Frontiers in Cardiovascular Medicine, 2022)
Very-low-density lipoprotein (VLDL) is the only lipoprotein containing apolipoprotein B that is secreted from the liver, where VLDL is assembled from apolipoproteins, cholesterol, and triglycerides. The primary function of VLDL is to transport cholesterol and other lipids to organs and cells for utilization. Apart from its role in normal biologic processes, VLDL is also known to contribute to the development of atherosclerotic cardiovascular disease. Large VLDL particles, which are subclassified according to their size by nuclear magnetic resonance spectrometry, are significantly correlated not only with atherosclerosis, but also with insulin resistance and diabetes incidence. VLDL can also be subclassified according to surface electrical charge by using anion-exchange chromatography. The most electronegative VLDL subclass is highly cytotoxic to endothelial cells and may contribute to coronary heart disease. In addition, electronegative VLDL contributes to the development of atrial remodeling, especially in patients with metabolic syndrome, which is an established risk factor for atrial fibrillation. In this review, we focus on the VLDL subclasses that are associated with apolipoprotein alterations and are involved in cardiovascular disease. The postprandial enhancement of VLDL's pathogenicity is a critical medical issue, especially in patients with metabolic syndrome. Therefore, the significance of the postprandial modification of VLDL’s chemical and functional properties is extensively discussed.